Ichnofossils Characteristics in Pelagic Siliciclastic Carbonate Turbidites of Weda Formation, Halmahera Island - Angga Jati Widiatama; Lauti Dwita Santy; Aries Kusworo (JURNAL RISET GEOLOGI DAN PERTAMBANGAN, 2022)
The Weda Formation in Lili River, Dorosagu, East Halmahera consists of siliciclastic and pelagic carbonates deposited in a submarine fan environment. Research on the Weda Formation in the northern part of Halmahera Island is relatively minimal because most of the research about this formation has been carried out in the southern part of Halmahera Island. The lack of road access and its remote location have resulted in the lack of intensive research on this formation. This study aims to determine the relationship between the intensity and diversity of trace fossils in the submarine fan facies association of the Weda Formation. Sedimentological studies include sedimentary texture, sedimentary structure, turbidite material type, and layer thickness. While the study of trace fossils includes the identification of trace fossil types, classification of behavior, intensity, and diversity in sedimentary layers, and the factors that influence them during deposition. There are eight types of ichnofossil observed in the Lili River, Ophiomorpha, Thalassinoides, Rhizocorallium, Palaeophycus, Zoophycos, Chondrites, Lorenzinia, and Spirorhaphe, which are found in three facies associations (AF): submarine fan channel facies association (AF1), submarine fan lobe facies association (AF2), and submarine fan distal facies association (FA3). The submarine fan channel facies is characterized by the presence of Ophiomorpha and Thalassinoides which present in low intensity and low diversity due to unstable environmental conditions-high stress due to intensive turbidite currents. The submarine fan lobe facies shows a higher density and diversity where ichnofossil is classified into two based on the substrate in the flysch deposits. Rhizocorallium, Thalassinoides, and Palaeophycus ichnofossil were formed in the sand substrate, while Zoophycos and Chondrites ichnofossil were formed in the shale substrate. Palaeophycus, Zoophycos, Chondrites, Lorenzinia, and Spirorhaphe ichnofossil were found in the submarine fan distal facies associated with high intensity indicating low energy levels and low sedimentation rates.